Safety profiles of the new target therapies—pemigatinib, futibatinib, and ivosidenib—for the treatment of cholangiocarcinoma: a systematic review - Giulia Matranga; Anna Carollo; Miriam Alaimo; Sofia Cutaia; Sergio Rizzo; Alessio Provenzani (Therapeutic Advances in Drug Safety)
Background: Cholangiocarcinoma (CCA) is a cancer with a low survival rate. New drugs targeting molecular alterations, oncogenic mutations, and gene fusions are being tested as second-line treatments. Objectives: This systematic review aims to summarize the results obtained with three new targeted therapies—pemigatinib, futibatinib, and ivosidenib—for the treatment of CCA, evaluating their safety and tolerability profiles in patients, compared to current standard therapies. Data sources and methods: A systematic literature search was performed with a cutoff date of July 24, 2023, in MEDLINE, Embase, and the Cochrane Library. The authors also conducted an advanced search in the ClinicalTrials.gov database, evaluated conference abstracts, article bibliographies, and drug monographs. Studies involving the treatment of patients with pemigatinib, futibatinib, and ivosidenib were considered. The selected studies had to report adverse events (AEs) that occurred during treatment with these therapies. Results: The most common AEs observed with pemigatinib, futibatinib, and ivosidenib were alopecia, diarrhea, fatigue, and dysgeusia. In addition, hyperphosphatemia, hypophosphatemia, and ocular disorders were observed with fibroblast growth factor receptor (FGFR) inhibitors, while the isocitrate dehydrogenase 1 (IDH1) inhibitor was associated with dose-dependent prolongation of the corrected QT interval (QTc). These AEs were effectively managed through dose adjustments. Conclusion: FGFR2 and IDH1 inhibitors have good tolerability in the population examined. All AEs were optimally managed with dose modulation. Future studies should focus on identifying the most effective dosages to further enhance treatment safety.